Attracting women to STEM programs: the influence of goal-orientations and the use of gendered wording in recruitment materials - Krome, Lesly R. (Kansas State University, 2016)
Recruiters and recruitment materials can signal to job seekers certain aspects of the organization which may affect how attractive the organization appears as a potential employer (signaling theory; Rynes, Bretz, & Gerhart, 1991). Some signals received during recruitment can indicate that social-based inequalities and hierarchies may exist (social dominance theory; Sidanius & Pratto, 1999). It is possible that women might perceive themselves as part of a subordinate group in fields where they are underrepresented, such as the areas of science, technology, engineering, and mathematics (STEM). The current research examines participant gender and the effects of using traditionally feminine words, masculine words, or neutral words in recruitment material on participants’ ratings of STEM program attractiveness and perceptions of institutional belonging. Furthermore, one’s goal orientation can influence the type of goal one is attracted to and whether it will be adopted; the current research looks at the effects of one’s goal orientation and how that is related to the person’s efficacy regarding STEM recruitment materials (Elliott & Dweck, 1988). Additionally, a goal orientation intervention was conducted in an attempt to influence participants’ situational learning goal orientations and measured efficacy. While the gendered wording of the recruitment material did not influence participants’ ratings of attraction and perceived belongingness, women rated the STEM recruitment material as more attractive than men. Additionally, participants’ learning goal orientation was found to have a significant influence on their measured efficacy. The results of this research have implications for recruiting female applicants to STEM programs/careers and suggestions for organizational interventions and best practices in order to positively affect job outcomes.
Keywords: recruiting; signaling theory; goal orientation; social dominance theory; STEM; gendered wording